2010
DOI: 10.1158/1538-7445.am10-4625
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 4625: A biotin-label-based antibody array for high-content profiling of protein expression

Abstract: Profiling protein expression on a global scale will have significant impact on biomedical research, particularly in the discovery and development of drugs and biomarkers. Through the years, several antibody array systems have been invented and developed for multiple protein detection. However, a reliable and high-content system for protein profiling from many biological samples has yet developed. To address this problem, we have developed a high density antibody array and used this technology to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 0 publications
0
43
0
Order By: Relevance
“…Because the cross-reactivity is eliminated in the label-based format, array densities can be scaled up to a theoretically unlimited size. Both the label-based method [33] and the sandwich-based method [34] have proven valuable in the discovery of disease biomarkers.…”
Section: Antibody Array Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…Because the cross-reactivity is eliminated in the label-based format, array densities can be scaled up to a theoretically unlimited size. Both the label-based method [33] and the sandwich-based method [34] have proven valuable in the discovery of disease biomarkers.…”
Section: Antibody Array Technologymentioning
confidence: 99%
“…A panel of protein expression showed significant difference between normal and cancer (P<0.05). By classification analysis and split-point score analysis of these two groups, a six-marker panel of proteins (IL-2R , endothelin, osteoprotegerin, vascular endothelial growth factor D (VEGF-D) and betacellulin (BTC)) could be used to distinguish ovarian cancer patients from normal subjects [33]. Those studies strongly suggest that antibody array technology has great promise in the discovery and development of ovarian cancer biomarkers.…”
Section: Cytokine Antibody Arrays In Cancer Bio-marker Discoverymentioning
confidence: 99%
“…Multiple studies have been reported to identify serum ovarian cancer biomarkers using multiplex antibody array technology [7-9]. Dr. Lokshin’s group identified a group of 6 serum protein markers, including interleukin-6 (IL-6), interleukin-8 (IL-8), epidermal growth factor (EGF), vascular endothelial growth factor (VEGF), monocyte chemoattractant protein-1 (MCP-1), and CA-125, which displayed significant difference in serum concentrations between ovarian cancer and control groups with 84% sensitivity at 95% specificity [7].…”
Section: Introductionmentioning
confidence: 99%
“…Using human biotin-based antibody arrays, we screened the serum expression profiles of 507 proteins in serum samples from 47 patients with ovarian cancers, 33 patients with benign ovarian masses and 39 healthy, age-matched controls and identified significant differences in protein expression between normal controls and patients with ovarian cancer ( P <0.05). By classification analysis and split-point score analysis of these 2 groups, a 6-marker panel of proteins, which consisted of interleukin-2 receptor alpha (IL2Rα), endothelin, osteoprotegerin (OPG), vascular endothelial growth factor D (VEGF-D) and betacellulin (BTC), can be used to distinguish ovarian cancer patients from normal subjects [9]. These studies strongly suggest that antibody array technology has shown great promise in the discovery and development of serum ovarian cancer biomarker profiles and strongly suggest that serum cytokine panels may be useful as biomarkers for early detection of ovarian cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, nowadays microarrays are used to measure events at the post-transcriptional level of gene regulation (e.g. miRNA expression [1]), at the post-translational level by measuring active protein levels (antibody arrays [2]) or I. Valavanis is with the Institute of Biological Research and Biotechnology, National Hellenic Research Foundation, Athens, Greece (email: ivalavan@eie.gr).…”
Section: Introductionmentioning
confidence: 99%